2013
DOI: 10.1017/s1365100512000600
|View full text |Cite
|
Sign up to set email alerts
|

The Price–marginal Cost Markup and Its Determinants in U.S. Manufacturing

Abstract: This paper estimates the price-marginal cost markup for US manufacturing using a new methodology. Most existing techniques of estimating the markup are a variant on Hall's (1988) framework involving the manipulation of the Solow Residual. However this paper argues that this notion is based on the unreasonable assumption that labor can be costlessly adjusted at a fixed wage rate. By relaxing this assumption, we are able to derive a generalized markup index, which when estimated using manufacturing data is highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
3
7
0
1
Order By: Relevance
“…Not only is this observation consistent with U.S. experience (e.g., Rotemberg and Woodford, 1999;Mazumder, 2014), recent studies have demonstrated that it also strengthens the model's internal propagation mechanisms. Ravn et al (2006) show that by inducing countercyclical mark-ups, deep habits can account for the observed procyclical responses of consumption and wages to a government spending shock.…”
Section: Introductionsupporting
confidence: 79%
“…Not only is this observation consistent with U.S. experience (e.g., Rotemberg and Woodford, 1999;Mazumder, 2014), recent studies have demonstrated that it also strengthens the model's internal propagation mechanisms. Ravn et al (2006) show that by inducing countercyclical mark-ups, deep habits can account for the observed procyclical responses of consumption and wages to a government spending shock.…”
Section: Introductionsupporting
confidence: 79%
“…Shapiro (1987) and Norrbin (1993) estimated a positive price-cost margin exercised by the US manufacturing sectors suggesting that the market structure corresponds to imperfect competition. Mazumder (2014) supports the presence of countercyclical and falling markups since the 1960s because the price-cost margin depends on the share of manufacturing imports. For this reason, the increase of foreign competition over the years forced the US firms to adjust their price level downwards, thus converging to perfect competition.…”
Section: Literature Reviewmentioning
confidence: 76%
“…Existing research documents that trade liberalization has significant effects on firm behavior and performance through an increase in competition. Notably, trade liberalization stimulates firm innovation, productivity, and efficiency, while helping to lower product prices and firm costs, thereby affecting firm markups (Saggay, Heshmati, and Dhif 2007;Mazumder 2014;Edmond, Midrigan, and Xu 2015;De Loecker and others 2016). Trade liberalization is, thus, usually a major element of product market and competition reforms.…”
Section: Box 21 Firm Markups and Trade Liberalizationmentioning
confidence: 99%